2014
DOI: 10.5539/gjhs.v6n5p55
|View full text |Cite
|
Sign up to set email alerts
|

General Health of Foreign-Origin Groups and Native Population

Abstract: Background:Since the mental health of marginal settlers (non-native population) may affect other citizens’ health, the present study attempts to investigate the mental health status of marginal settlers of Yazd.Materials and Methods:this study was a descriptive, cross-sectional research, in which 400 of non-native and native population have participated. To study mental health status of people, a questionnaire was used. The first section of this questionnaire was the 28-item questionnaire of GHQ and the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The main reason for the lack of realizing this goal is not to address unsafe and poor quality care. In a study, 1 it was observed that about 98% of stillbirths occur in low- and middle-income countries, but in Yazd province, which has relatively acceptable economic, health, and cultural indicators compared to other provinces of Iran, 10 the Stillbirth Rate is relatively high compared to the national Stillbirth Rate. 13 , 14 According to data from our participants, they have given birth to 19 377 children during their lifetime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

Investigation of Factors Related to Stillbirth

Torkashvand Moradabadi,
Ardian,
Mazloomy-Mahmoodabad
et al. 2024
INQUIRY
Self Cite
“…The main reason for the lack of realizing this goal is not to address unsafe and poor quality care. In a study, 1 it was observed that about 98% of stillbirths occur in low- and middle-income countries, but in Yazd province, which has relatively acceptable economic, health, and cultural indicators compared to other provinces of Iran, 10 the Stillbirth Rate is relatively high compared to the national Stillbirth Rate. 13 , 14 According to data from our participants, they have given birth to 19 377 children during their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the factors related to stillbirth in Yazd province and also the cities of this industrial and immigrant-attracting province 10 have not been investigated recently.…”
Section: Introductionmentioning
confidence: 99%

Investigation of Factors Related to Stillbirth

Torkashvand Moradabadi,
Ardian,
Mazloomy-Mahmoodabad
et al. 2024
INQUIRY
Self Cite
“…To answer the question of why women who file divorce petitions more frequently than men in Iranian society have adopted a different attitude toward divorce in the recent years. Despite the fact that divorce is discouraged according to the religious teachings and moral principles of the society, it can be argued that the values related to the maintenance and stability of the family with respect to the fundamental functions of the family undergo a transformation under the influence of globalization and modernization, and eventually influence the change in attitudes toward divorce (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Reliability refers to the consistency and coincidence within the constructs of an instrument [ 20 ]. In a study conducted in 5 countries, the internal consistency of the TPB was obtained from 0.52 to 0.89 [ 21 ] [ 22 ]. The results showed that three constructs were significantly reliable, but under the theme of subjective norms, the estimated alpha was 0.63.…”
Section: Discussionmentioning
confidence: 99%